GAMBARAN TINGKAT PENGETAHUAN TENAGA TEKNIS KEFARMASIAN TENTANG TINDAKAN ASEPTIC DISPENSING DI RS UMUM DAERAH DR. MOEWARDI - Ina Damayanti (Jurnal Farmasi (Journal of Pharmacy), 2022)
Safe handling of parenteral preparations needs to be done in a disciplined and careful manner to prevent unwanted risks, Human resources are a very important part in the implementation of sterile preparations dispensing services, it is necessary to understand aseptic actions in the mixing process with applicable procedures to avoid the dangers of pyrogens and contaminants as well as prevent medication errors. This study aims to determine pharmaceutical technician knowledge about aseptic dispensing at RSUD Dr. Morwardi. This research is a non experimental research with a descriptive survey design. The sampling technique in this research is total sampling. The sample in this study amounted to 50 people. Respondent’s knowledge data was collected using a questionnaire with a total of 10 questions that had been tested for validity with Pearson’s correlation and reliability test with Cronbach’s Alpha which was then analized using SPSS 25. The results showed that knowledge about standard precautions was good, as many as 44 people (88%). Respondents with sufficient knowledge were 4 people (8%), and with poor knowledge were 2 people (4%). The conclusion of this study is that the level of knowledge of pharmaceutical technician about aseptic dispensing at RSUD Dr. Moewardi is good.